2016
DOI: 10.18632/oncotarget.11630
|View full text |Cite
|
Sign up to set email alerts
|

Loss of long noncoding RNA FOXF1-AS1 regulates epithelial-mesenchymal transition, stemness and metastasis of non-small cell lung cancer cells

Abstract: Although recent evidence shows that long noncoding RNAs (lncRNAs) are involved in the regulation of gene expression and cancer progression, the understanding of the role of lncRNAs in lung cancer metastasis is still limited. To identify novel lncRNAs in non-small cell lung cancer (NSCLC), we profile NSCLC tumor and matched normal samples using GeneChip® Human Gene 2.0 ST Array, which provides the most accurate, sensitive, and comprehensive measurement of protein coding and lncRNA transcripts. We identified a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…Recently, in lung cancer, a lncRNA expression profiling identified to FENDRR as one of the lncRNAs were differentially expressed between cancer and the adjacent normal tissues [13]. Additionally, also in lung cancer, FENDRR expression was associated with tumour migration and metastasis [14]. However, the overall contributions of FENDRR to lung cancer remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in lung cancer, a lncRNA expression profiling identified to FENDRR as one of the lncRNAs were differentially expressed between cancer and the adjacent normal tissues [13]. Additionally, also in lung cancer, FENDRR expression was associated with tumour migration and metastasis [14]. However, the overall contributions of FENDRR to lung cancer remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…FOXF1-AS1 was associated with lung cancer cell migration and invasion by regulating EMT. Interestingly, we also found that FOXF1-AS1 might regulate EMT, stemness and metastasis of NSCLC cells via EZH2, indicating it as a therapeutic target for future treatment of NSCLC [11].…”
Section: Foxf1-as1mentioning
confidence: 67%
“…LncRNAs have been reported to be involved in multiple biological processes such as development and progression of human malignancies [7,8]. Although the potential functions of lncRNAs are still enigmatic in NSCLC, an increasing number of studies have now demonstrated that lncRNAs play a major role in development and progression of NSCLC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These transcripts may also be further investigated as putative MDR-biomarkers. Interestingly, four of these transcripts were previously associated with the regulation of tumor cell proliferation [42], epithelial-mesenchymal transition [43], stemness [43], metastization [43][44][45], poor prognosis [44], and poor survival [46].…”
Section: Discussionmentioning
confidence: 99%